Macrocyclic alkanes in crude oils and sediment extracts: enrichment using molecular sieves - Audino, Michiele; Grice, Kliti; Alexander, Robert; Kagi, Robert (Elsevier, 2004)
A molecular sieve method using NaX (13X) has been used to separate macrocyclic alkanes (in the carbon number range C14?C34), markers of the freshwater alga Botryococcus braunii, from the branched/cyclic hydrocarbon fractions of sediments and crude oils. The macrocyclic alkanes were included in the 13X sieve and were recovered by HF digestion.